Mewujudkan Efektivitas Penegakan Hukum Perjudian Online di Indonesia - Dedi Aringga, Rino; El Walad Meuraksa , M. Amin (Program Studi Hukum Universitas Pamulang, 2024)
Online gambling is an increasingly rampant phenomenon in Indonesia, with widespread negative impacts on individuals and society. This article explores the challenges in law enforcement against online gambling in Indonesia and presents strategies to improve the effectiveness of law enforcement. Through a literature review, case analysis, and lessons learned, this article concludes that strengthening inter-agency cooperation, increasing public awareness, and developing law enforcement technology are key to addressing these challenges.